2017
DOI: 10.14814/phy2.13411
|View full text |Cite
|
Sign up to set email alerts
|

Association of urinary citrate excretion, pH, and net gastrointestinal alkali absorption with diet, diuretic use, and blood glucose concentration

Abstract: Urinary citrate (Ucit) protects against urinary stone formation. Acid base status and diet influence Ucit. However, the effect of demographics, diet, and glucose metabolism on Ucit excretion, urinary pH (U‐pH) and net gastrointestinal alkali absorption (NAA) are not known. Twenty‐four hour urine samples, blood glucose, creatinine, and cystatin C were obtained from non‐Hispanic white sibships in Rochester, MN (n = 446; 64.5 ± 9 years; 58% female). Diet was assessed by a food frequency questionnaire. The impact … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…In a study on 446 participants (11.5% of whom were with a history of kidney stones), Perinpam et al found that net gastrointestinal alkali absorption was directly associated with urine pH and citrate, similar to our findings; however, that study only partially accounted for differences in dietary acid load by adjustment for dietary potassium intake and did not analyze differences between the (very few) stone formers and non–stone formers. 7 Sakhaee et al reported a direct association between net gastrointestinal alkali absorption and urine citrate in 131 non–stone formers and in idiopathic hypocitraturic stone formers, but not in patients affected by distal renal tubular acidosis. However, in that study, the authors did not control for differences in dietary intakes, and in fact, net gastrointestinal alkali absorption was used as a marker of dietary intake of potential alkali.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study on 446 participants (11.5% of whom were with a history of kidney stones), Perinpam et al found that net gastrointestinal alkali absorption was directly associated with urine pH and citrate, similar to our findings; however, that study only partially accounted for differences in dietary acid load by adjustment for dietary potassium intake and did not analyze differences between the (very few) stone formers and non–stone formers. 7 Sakhaee et al reported a direct association between net gastrointestinal alkali absorption and urine citrate in 131 non–stone formers and in idiopathic hypocitraturic stone formers, but not in patients affected by distal renal tubular acidosis. However, in that study, the authors did not control for differences in dietary intakes, and in fact, net gastrointestinal alkali absorption was used as a marker of dietary intake of potential alkali.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, it could be hypothesized that the Oh equation for net gastrointestinal alkali absorption estimation is not valid in stone formers because it incorporates urine chemistries that are known to be altered in those with kidney stones, such as calcium, potassium, magnesium, and phosphate. However, this approach has been used in the past to study net gastrointestinal alkali absorption in stone formers, 7,8 and balance studies on stool are difficult to perform. Furthermore, the relationship in the expected direction between net gastrointestinal alkali absorption and both urine pH and renal net acid excretion, which are not included in the calculation of net gastrointestinal alkali absorption, strengthens the validity of the net gastrointestinal alkali absorption calculation.…”
Section: Discussionmentioning
confidence: 99%
“…The above is due to the expansion of the aqueous urinary volume, which gives the activation of the sodium-hydrogen-ATPase antiporter, producing a hydrogen secretion and passive bicarbonate reabsorption. In the case of the Furosemide group, occurred an exchange of sodium and chlorine for hydrogenation in the collecting tubule, causing a slightly more acidic pH [14].…”
Section: Discussionmentioning
confidence: 99%